The Effect of Moringa Leaf Extract Administration on Sperm Morphology and Blood Glucose Reduction in Alloxan-Induced Sprague Dawley Rats - Wahab, Dinda Nuraini Hanifah; Hasanah, Uswatun; Harfiani, Erna; Thadeus, Maria Selvester (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractIncreased blood sugar levels can be triggered by increased intake or insulin resistance, leading to increased oxidative stress that affects sperm quality during spermatogenesis. Moringa oleifera, rich in antioxidants, has been proven effective in improving sperm quality through several studies. This study aims to evaluate the influence of moringa leaf extract on sperm morphology and the reduction of blood sugar levels in Sprague Dawley white rats (Rattus norvegicus) induced by alloxan. Fasting blood sugar tests showed that rats induced with alloxan without moringa leaf extract had the highest blood sugar levels among the groups. In contrast, the negative control and treatment groups with moringa leaf extract successfully maintained blood sugar levels at normal levels. Normal sperm morphology reached 94.5% in the treatment group with the highest dose of moringa leaf extract. The results of the study indicate a significant relationship between blood sugar levels and sperm morphology in alloxan-induced white rats after the administration of moringa leaf extract. Moringa oleifera has the potential to be a therapeutic intervention to improve sperm quality and control blood sugar levels in hyperglycemic conditions.AbstrakPeningkatan kadar gula darah dapat dipicu oleh peningkatan asupan atau resistensi insulin menyebabkan peningkatan stres oksidatif yang mempengaruhi kualitas sperma selama spermatogenesis. Tanaman kelor (Moringa oleifera), tumbuhan yang kaya akan antioksidan, telah terbukti efektif dalam meningkatkan kualitas sperma melalui beberapa penelitian. Penelitian ini bertujuan untuk mengevaluasi pengaruh ekstrak daun kelor terhadap morfologi sperma dan pengurangan kadar gula darah pada tikus putih Sprague Dawley (Rattus norvegicus) yang diinduksi aloksan. Uji gula darah puasa menunjukkan bahwa tikus yang diinduksi aloksan tanpa perlakuan ekstrak daun kelor memiliki kadar gula darah tertinggi di antara kelompok-kelompok lainnya. Sebaliknya, kelompok kontrol negatif dan kelompok perlakuan dengan ekstrak daun kelor berhasil menjaga kadar gula darah pada tingkat normal. Morfologi sperma normal mencapai 94,5% pada kelompok perlakuan dengan dosis 400 mg/kgBB ekstrak daun kelor. Kesimpulan yang didapatkan pada penelitian ini berkaitan dengan temuan hubungan signifikan antara kadar gula darah dan morfologi sperma pada tikus putih yang diinduksi aloksan setelah pemberian ekstrak daun kelor. Tanaman kelor (Moringa oleifera) memiliki potensi sebagai intervensi terapeutik untuk meningkatkan kualitas sperma dan mengendalikan kadar gula darah dalam kondisi hiperglikemia.